1998
DOI: 10.1016/s1097-2765(00)80043-x
|View full text |Cite
|
Sign up to set email alerts
|

Ribozyme Catalysis from the Major Groove of Group II Intron Domain 5

Abstract: The most highly conserved nucleotides in D5, an essential active site component of group II introns, consist of an AGC triad, of which the G is invariant. To understand how this G participates in catalysis, the mechanistic contribution of its functional groups was examined. We observed that the exocyclic amine of G participates in ground state interactions that stabilize D5 binding from the minor groove. In contrast, each major groove heteroatom of the critical G (specifically N7 or O6) is essential for chemis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
72
2
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 83 publications
(81 citation statements)
references
References 60 publications
6
72
2
1
Order By: Relevance
“…This nucleotide is highly conserved, forming a wobble pair with U32, and part of the so-called AGC or catalytic triad. Its minor groove site is involved in tertiary contacts whereas the major groove is implicated to harbour the catalytic site [68]. Our NOESY data under these conditions does not support a higher dynamics or even flipping out of G3, as it has been suggested previously [69], but shows an intact GU wobble pair.…”
Section: <>contrasting
confidence: 63%
“…This nucleotide is highly conserved, forming a wobble pair with U32, and part of the so-called AGC or catalytic triad. Its minor groove site is involved in tertiary contacts whereas the major groove is implicated to harbour the catalytic site [68]. Our NOESY data under these conditions does not support a higher dynamics or even flipping out of G3, as it has been suggested previously [69], but shows an intact GU wobble pair.…”
Section: <>contrasting
confidence: 63%
“…In spite of the high conservation of the structure of this element and the apparent conservation of its function as shown by these studies, we do not have a clear idea of what its function might be in the spliceosome+ Its location near the sites of splicing chemistry have led to speculation that it plays a role in the active site of the spliceosome (reviewed in Nilsen, 1998;Collins & Guthrie, 2000)+ Several groups have suggested parallels with features of various ribozymes including the hairpin ribozyme (Tani & Ohshima, 1991;Sun & Manley, 1995) and domain 5 of group II self-splicing introns (see discussions in Sun & Manley, 1997;Costa et al+, 1998;Nilsen, 1998)+ The group II domain 5 comparison is particularly interesting+ A recent revision of the proposed structure of the domain 5 stem-loop has emphasized the similarity between it and the U6 (or U6atac) intramolecular stem-loop (Costa et al+, 1998)+ A phosphorothioate modification-interference study of domain 5 in self-splicing identified a phosphate group in the bulge region as important for splicing catalysis (Chanfreau & Jacquier, 1994)+ This phosphate is located in a very similar position to one identified as important for U6 snRNA function in in vitro pre-mRNA splicing in both yeast (Fabrizio & Abelson, 1992) and nematodes (Yu et al+, 1995)+ Recent investigations of both phosphorothioate diastereomers at this position in yeast U6 snRNA have revealed a metal ion specificity switch for the first step of splicing (Yean et al+, 2000)+ This suggests that U6 snRNA participates in the catalysis of splicing through metal ion coordination and places this stem-loop element at or very near the catalytic center of the spliceosome+ Pyle's group has also suggested that the bulge and lower stem regions of domain 5 serve to position a critical metal ion for group II splicing (Konforti et al+, 1998)+ Such a function would mainly involve the positioning of phosphate groups to coordinate the metal and would be compatible with many but perhaps not all base paired sequences within the stem region+ Basespecific interactions would be limited to residues in unpaired regions and functional groups in the major and minor groves of the helical regions+ Such a function would fit with the apparent tolerance of the stem regions of U6atac snRNA for many but not all substitutions that maintain base pairing+…”
Section: Discussionmentioning
confidence: 99%
“…Also, DV with the bulged nucleotides (purple in Fig. 7) and the catalytic triad of DV, which are known to play a major role in catalysis (Chanfreau and Jacquier 1994;Konforti et al 1998;Sigel et al 2004), is shown. The intron was crystallized in the presence of Ca 2+ ions, which inhibit the splicing reaction (Erat and Sigel 2008) and represent the conformation before the first splicing step.…”
Section: Parallels To the Crystal Structure Of The O Iheyensis Groupmentioning
confidence: 99%